I am not a Paranoid A Case Study on People with Schizophrenia Social Welfare Problem - Sunit Agus Tri Cahyono; Asrap Asrap (Balai Besar Penelitian dan Pengembangan Pelayanan Kesejahteraan Sosial, Kementerian Sosial, 2015)
As chronic and relapsing mental disturbance, schizophrenia has social malfunction impact on the people with it. That condition effects on family welfare. This research is meant to know the cause of schizophrenia, and to know family support to overcome people with schizophrenia. Methodologically, this research uses qualitative approach by mean of case study. Informants are people with schizophrenia, their family, their neighbors, and therapists PSBK. The research finds that multi dimension factors that process and interact each other as the main factors people suffer from schizophrenia. Family psychological-social support that is not maximum because lack of accurate understanding and information on phenomenon, ill process, psychological-medic assistance, and rehabilitation directory to people with schizophrenia. Each member of the family need take role as caregiver who is able to understand the problem and fulfill life needs of people with schizophrenia, is the recommendation posed in this research.